Meta-analysis of the procedural risks of carotid endarterectomy and carotid artery stenting over time. Issue 1 (4th December 2017) - Lokuge, K; de Waard, D D; Halliday, A; Gray, A; Bulbulia, R; Mihaylova, B
Abstract: Background: Stroke/death rates within 30 days of carotid endarterectomy (CEA) and carotid artery stenting (CAS) in RCTs inform current clinical guidelines. However, the risks may have changed in recent years with wider use of effective stroke prevention therapies, especially statins, improved patient selection and growing operator expertise. The aim of this study was to investigate whether the procedural stroke/death risks from CEA and CAS have changed over time. Methods: MEDLINE and Embase were searched systematically from inception to May 2016 for observational cohort studies of CEA and CAS. Studies included reported on more than 1000 patients, with 30-day outcomes after the procedure according to patients' symptom status (recent stroke or transient ischaemic attack). Restricted maximum likelihood random-effects and meta-regressions methods were used to synthesize procedural stroke/death rates of CEA and CAS according to year of study recruitment completion. Results: Fifty-one studies, including 223 313 patients undergoing CEA and 72 961 undergoing CAS, were reviewed. Procedural stroke/death risks of CEA decreased over time in symptomatic and asymptomatic patients. Risks were substantially lower in studies completing recruitment in 2005 or later, both in symptomatic (5·11 per cent before 2005 versus 2·68 per cent from 2005 onwards; P = 0·002) and asymptomatic (3·17 versus 1·50 per cent; P < 0·001) patients. Procedural stroke/death rates of CAS did not change significantly over time (4·77 per cent among symptomatic and 2·59 per cent among asymptomatic patients). There was substantial heterogeneity in event rates and recruitment periods were long. Conclusions: Risks of procedural stroke/death following CEA appear to have decreased substantially. There was no evidence of a change in stroke/death rates following CAS. Abstract : Endarterectomy outcomes improving